Evaluasi Kualitas Susu Kambing Etawa Yang Dikoleksi dari Peternakan Berskala Kecil Di Wilayah Samigaluh, Kulon Progo - Nur Ika Prihanani; Risa Ummami; Naela Wanda Yusria Dalimunthe; Muhammad Rosyid Ridlo (Jurnal Nasional Teknologi Terapan (JNTT), 2019)
Peranakan Etawa (PE) Goat is a type of superior goat that is very potential to be maintained as a dairy goat. Food safety guarantee of animal origin becomes very important in order to prevent and spread disease from animal to human. So it takes an effort in terms of quality control of food of animal origin, especially goat's milk. This study aims to determine the quality of PE goat milk which is maintained by farmers in small farms. The study was conducted on 15 samples of goat milk collected in the region of Samigaluh, Kulon Progo. The research used a method of testing the quality of milk in the laboratory that includes testing the physical condition of milk and milk composition. Testing the physical condition of milk consists of testing of cleanliness, color, odor, and taste. Testing of milk composition consist of degree of acid, reductase, fat content, calculation of total bacteria by Total Plate Count (TPC) method. The data obtained are then analyzed descriptively. The results showed milk samples were clean, yellowish, typical odor of fresh milk, and had a slightly sweet taste. Mean of acid degree 7,1°SH, mean of reductase rate 2 hour, mean of fat content 4,53% and mean total bacteria 2,8 x 105 CFU ml. These results indicate that the quality of goat milk included in the category worth to be consumed with sufficient quality. The quality of goat's milk is influenced by the type of feed given and the nutrient composition in the feed type.